Synthesis optimization for reduced graphene oxide-based electrodes from surface modified silica fibers - De la Torre Oyola, María José (2021)
In this thesis work, it is proposed an innovative methodology for the preparation of reduced graphene oxide optimized for surface modified silica nanoelectrodes (rGO/OF). Aqueous chemical reduction of graphene oxide (GO) was carried by using sodium borohydride as a function of time from 3 h to 42 h, in order to recover the electrical properties of graphene. Samples of rGO/OF were characterized in Raman spectroscopy. Raman spectra results showed that the longer the reduction time it is possible to obtain a graphitic material with fewer oxygen-containing functional groups. The optical fiber (OF) surface was modified by treatment at 700 ◦C in an oxidizing environment and 1:3 piranha solution for polymeric coatings removal; and subsequently (3-aminopropyl)triethoxysilane (APTES) was used for adhesion of concentric rGO to the OF. The characterization results confirm the feasibility of rGO as a conductive material for miniaturized sensing devices.